2018
DOI: 10.1038/s41388-018-0230-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel tumour suppressive protein encoded by circular RNA, circ-SHPRH, in glioblastomas

Abstract: The previously unchartered gene expression territory governed by circular RNAs is becoming clearer with the onset of deeper sequencing technologies. The translation of circular RNAs remained a controversial theory until earlier this year, when two studies [1, 2] showed endogenous circular RNA translation in vitro and in vivo, and have further provided mechanistical evidence. In this edition of Oncogene, Zhang et al., provide evidence for the first circular RNA translated with relevance to cancer; a novel tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 13 publications
0
72
0
1
Order By: Relevance
“…It also stabilizes SHPRH as an E3 ligase by ubiquitinating proliferating cell nuclear antigen. In this manner, it inhibits cell proliferation and tumorigenicity [68,169] (Fig. 1a).…”
Section: Shprh-146aamentioning
confidence: 93%
“…It also stabilizes SHPRH as an E3 ligase by ubiquitinating proliferating cell nuclear antigen. In this manner, it inhibits cell proliferation and tumorigenicity [68,169] (Fig. 1a).…”
Section: Shprh-146aamentioning
confidence: 93%
“…However, an increasing number of studies have revealed that some circRNAs could be translated into proteins in a cap‐independent manner (Begum et al, ; C. Y. Chen & Sarnow, ; Legnini et al, ; Yang et al, ). In fact, this may be unsurprising since the vast majority of circRNAs are exon derivates and are located in the cytoplasm where translation takes place (Begum et al, ; Pamudurti et al, ; Yang et al, ). Interestingly, scientists have shown that circ‐SHPRH (M. Zhang et al, ) could be translated into a 146aa protein with overlapping genetic codes, similar to viral RNAs.…”
Section: Functionmentioning
confidence: 99%
“…An increased patient survival was observed with elevated levels of SHPRH-146aa in glioblastoma patients. 196,197 Collectively, these results showed that circRNA was a group of important regulatory factor and related to the occurrence and progression of glioblastoma. Thus, circRNA could serve as potential and valuable biomarker for diagnosis and treatment for glioblastoma patients in the future.…”
Section: Glioblastomamentioning
confidence: 81%
“…CircRNA containing an ORF could translate a functional protein through driving by Internal Ribosome Entry Site (IRES) elements. 196 For example, circ-SHPRH could produce a 17 kDa protein, the circular form of the SNF2 histone linker PHD RING helicase (SHPRH) gene encoded a novel protein that we termed SHPRH-146aa, which was a tumor suppressor in human glioblastoma. Excessive expressed SHPRH-146aa reduced malignant behavior and tumorigenicity in U251 and U373 glioblastoma cells by protecting SHPRH from degradation through the ubiquitin proteasome.…”
Section: Glioblastomamentioning
confidence: 99%